The Impact of Challenge and Hindrance Stressors on Thriving at Work Double Mediation Based on Affect and Motivation - Yang, Yi; Li, Xiang (Frontiers in Psychology, 2021)
Although the relationship betwwen stressors and thriving at work has been established, the linkage between them is still in the early stages of theory development. This study proposed a two-path model, based on Lepine's stressors-performance model, to analyze the effects of the stressors on the thriving at work. Two complementary mediating paths were proposed, i.e., affective strain (positive affect) and motivation (self-efficacy), which were explained using affective events theory and expectancy theory, respectively. Based on the empirical data from 233 employees, the results show that challenge stressors could enhance employees' positive affect and self-efficacy, thus leading to thriving at work; on the contrary, hindrance stressors would result in negative influences. In addition, it is also found that the effect of affective path tend to be greater than that of motivation path, which could provide a practical guide for organizations to effectively apply stress management and to promote employees thriving at work.